A systematic review of risk factors, obstetric and perinatal outcomes in COVID-19 infection in pregnancy - Koothan, Vijaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
While most women affected with COVID-19 during pregnancy have a mild illness 14% develop a severe critical illness that required hospitalization and oxygen support, and 5% of patients mandate intensive care. With more exposure to the illness in pregnancy, the clinical and treatment outcomes are changing. This review analyses the obstetric outcomes and risk factors reported recently from the literature, 185 potentially relevant articles published from January 2020 to August 2021 were reviewed. And 13 articles potentially eligible for inclusion underwent full-text review /cohorts/case series of not less than 9 cases that met the search criteria were included in the quantitative analysis. The range of the number of cases per population was 9,2475. A total of 4703 pregnant women with gestational age above 20 weeks and SARI/critical cases reported were 2589 cases. Outcomes in pregnant women with COVID-19 infection are not essentially different from non-pregnant women of similar age. Very few studies suggest vertical transmission as a possibility but the neonatal outcome is largely unaffected. Caesarean section rate has been coming down from 85.9% to 22% in recent times of which one-third of them was attributed to COVID-19 infections directly. Preterm labor was not found to be an independent risk factor for COVID-19 infection in the second COVID-19 wave. No increase in preterm birth in vaccinated pregnant women. Estimates of the overall case fatality ratio for COVID-19 appear to be in the range of 1-2% (0.5-10%) in high-income countries, and 2.4% in middle-income countries. Still, data regarding the impact on the fetal and neonatal outcomes of COVID-19 infection is unclear.